- #1

1/2"

- 99

- 0

## Homework Statement

The problem is

If x= 2+2

^{2/3}+2

^{1/3}

solve

x

^{3}-6x

^{ 2}+ 6x-2 =0

## Homework Equations

## The Attempt at a Solution

First i tried to substitute the values but its turning out to be really big( and i get quite scared when it turns up like this and so i didn't go any further this way)

then I tried to make a cube of x-1

Like this

x

^{3}-1 -3x

^{2}+ 3x-3x

^{ 2}+3x-1+x

^{3}=0

<==>(x-1)

^{3}+(x-1)

^{3}=x

^{3}

<==>2(x-1)

^{3}=x

^{3}

Well I can't get any further!

Happy if anyone helps!

Last edited: